2000
DOI: 10.1029/2000jb900177
|View full text |Cite
|
Sign up to set email alerts
|

Archeomagnetism of Ontario potsherds from the last 2000 years

Abstract: Abstract. An archeomagnetic study was carried out on potsherds samples from sites in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…The same procedures were followed for the second set of 60 specimens, Atm. is the heating atmosphere: A, air, H, helium; N is the number of points used in paleointensity determination; vT is the interval of temperature used in slope calculation; f and g are NRM fraction and gap factor, respectively [45]; SP is the quality factor de¢ned by Yu et al [46]; H þ c are the estimated paleointensity and its standard error after AARM correction. b The uncertainty in the mean is the standard deviation rather than the commonly used standard error [45].…”
Section: Paleointensity Experiments and Resultsmentioning
confidence: 99%
“…The same procedures were followed for the second set of 60 specimens, Atm. is the heating atmosphere: A, air, H, helium; N is the number of points used in paleointensity determination; vT is the interval of temperature used in slope calculation; f and g are NRM fraction and gap factor, respectively [45]; SP is the quality factor de¢ned by Yu et al [46]; H þ c are the estimated paleointensity and its standard error after AARM correction. b The uncertainty in the mean is the standard deviation rather than the commonly used standard error [45].…”
Section: Paleointensity Experiments and Resultsmentioning
confidence: 99%
“…In a palaeointensity study on older potsherds from Ontario, Yu and Dunlop (2000) concluded that there is no correlation between the degree of remanence anisotropy and the estimated palaeointensity value. However, in our study, we were able to show that the values of the correcting factor of palaeointensity determinations, even if is low, depend on the degree of remanent anisotropy and also on the angle between the NRM direction and the laboratory field direction.…”
Section: Discussionmentioning
confidence: 99%
“…Directional and intensity data obtained from these materials have been used to produce reference curves for the past few millennia. Reference curves (also called master curves), which reveal the variations in the intensity of the geomagnetic field are now available for several regions, including North America, Meso-America, Eastern Asia, Eastern and Western Europe (e.g., Kovacheva, 1997;Yu et al, 2000;Morales et al, 2001;Bowles et al, 2002;Genevey et al, 2003;Soler-Arechalde et al, 2006; see also the compilations of Valet, 2003;Perrin and Schnepp, 2004;. Archeointensity data for Western Europe are concentrated on archeological sites from France (e.g., Chauvin et al, 2000;Gallet et al, 2002;Genevey and Gallet, 2002;Gallet et al, 2005) while only few results are available for the Iberian Peninsula (Kovacheva et al, 1995;Gómez-Paccard et al, 2006).…”
Section: Introductionmentioning
confidence: 99%